Lithium metal surface interface protection material, lithium metal negative electrode material and preparation and application of lithium metal surface interface protection material and lithium metal negative electrode material
By transferring the copper phosphide array on the lithium metal foil and forming Cu particles surrounded by the Li3P network, a 3D hybrid ion/electronic conductive intermediate layer is constructed, which solves the safety problems of lithium dendrites generated during the circulation of lithium metal negative electrodes, and achieves higher stability and cycle life.
Patent Information
- Application Number
- CN202411681958.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-25
AI Technical Summary
The safety issues caused by the generation of lithium dendrites during the circulation process of lithium metal negative electrodes are an important issue restricting their commercial development. Existing methods such as high-temperature thermal perfusion or electrodeposition are at risk.
Through a room temperature mechanical rolling process, the copper phosphide (Cu3P) array is transferred on the lithium metal foil, and Cu particles surrounded by the lithium phosphide (Li3P) network are formed through the interface reaction between metals Li and Cu3P, and a 3D hybrid ion/electronic conductive intermediate layer is constructed.
This method is simple to operate, shortens the process flow and process time, improves the stability and cycle life of the lithium metal negative electrode, and the formed Li3P@MCI interface has higher stability and multiple ion channels, which significantly improves the transmission performance of Li ions.
Smart Images

Figure CN119506858A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium metal batteries, and specifically relates to a lithium metal surface interface protection material, a lithium metal negative electrode material, and preparation and application thereof. Background Art
[0002] As a negative electrode material, lithium metal has always attracted widespread attention due to its high negative equilibrium potential (-3.045V, relative to the standard hydrogen electrode) and high theoretical capacity (3860mAh / g). Especially in recent years, as the demand for battery energy density continues to increase, the capacity requirements for negative electrodes are also increasing, and metallic lithium is very necessary for commercial applications.
[0003] The safety issue caused by the formation of lithium dendrites during the cycle of lithium metal anode is an important issue restricting its commercial development. The formation of lithium dendrites is essentially a typical metal electrodeposition process, involving the transmission and electrochemical reduction of lithium ions at different interfaces. Since the reduction reaction can occur quickly on the electrode surface, the interface Li + The transmission and distribution of flux become the main factors determining the Li deposition behavior. However, the electrode surface usually has slow ion transmission and local uneven current distribution, which leads to ion fluctuations and the formation of uncontrollable dendrites. In order to avoid primary dendrites, it is generally necessary to design a conductive network layer that can evenly distribute the interface charge to achieve a relatively stable interface.
[0004] Recently, the concept of a hybrid electronic / ionic conductive interlayer has been proposed to better control the interfacial charge and realize a robust lithium metal anode. + The rapid dispersion and uniform current distribution significantly alleviate the interfacial Li + concentration gradient, which promotes the interfacial dynamics and more stable Li + However, high-temperature thermal perfusion or electrodeposition methods are usually used to pre-deposit Li in bones, which may be risky in complex procedures.
[0005] Therefore, there is an urgent need to provide a lithium metal surface interface protection material, a lithium metal negative electrode material, and their preparation and application. Summary of the invention
[0006] Based on the defects of the prior art, the first purpose of the present invention is to provide a method for preparing a lithium metal surface protection material; the second purpose of the present invention is to provide a lithium metal surface protection material prepared by the preparation method; the third purpose of the present invention is to provide a lithium metal negative electrode material; the fourth purpose of the present invention is to provide a lithium ion battery.
[0007] The purpose of the present invention is achieved through the following technical solutions:
[0008] In one aspect, the present invention provides a method for preparing a lithium metal surface protection material, comprising the following steps:
[0009] Step 1, soaking the copper foil in a hydrogen chloride solution, and then washing to remove impurities;
[0010] Step 2, mixing the ammonium persulfate solution and the sodium hydroxide solution to obtain a mixed solution;
[0011] Step 3: Place the copper foil after impurities removal into the mixed solution for reaction, and form a copper hydroxide layer on the surface of the copper foil. After washing and drying, the product is obtained, which is recorded as Cu(OH) 2 @Cu foil layer;
[0012] Step 4, Cu(OH) 2 @The Cu foil layer is placed at the end of the tube furnace, and an excess of sodium hypophosphite (analytical purity) is placed in the center of the tube furnace. The reaction is heated at high temperature under an inert gas atmosphere, and the product is obtained after cooling, which is recorded as Cu 3 P@Cu, namely lithium metal surface protection material.
[0013] In the above method, Cu 3 During the phosphating reaction synthesis of P@Cu, the interface of the copper foil synthesized by vapor phase phosphating is uniform, and the Cu 3 P is attached to the surface of copper foil. During the later rolling process and the synthesis process, Cu 3 The P array can be spontaneously transformed into Li 3 Nanoscale materials surrounded by P network.
[0014] In the above preparation method, preferably, in step 1, the concentration of the hydrogen chloride solution is 1-5M.
[0015] In the above preparation method, preferably, in step 1, washing is performed using deionized water and ethanol respectively.
[0016] In the above preparation method, preferably, in step 2, the concentration of the ammonium persulfate solution is 0.1-1M.
[0017] In the above preparation method, preferably, in step 2, the concentration of the sodium hydroxide solution is 2-10M.
[0018] In the above preparation method, preferably, in step three, the time for reacting the copper foil after impurities removal in the mixed solution is 5 to 30 minutes.
[0019] In the above preparation method, preferably, in step three, deionized water and ethanol are used for washing respectively.
[0020] In the above preparation method, preferably, in step three, drying is air-drying for 4 to 24 hours.
[0021] In the above preparation method, preferably, in step 4, the Cu(OH) 2 @The distance between the Cu foil layer and the sodium hypophosphite is 2 to 10 cm.
[0022] In the above preparation method, preferably, in step 4, the temperature of the tube furnace is set to 300-500° C.; the heating rate is 2-10° C. / min.
[0023] In the above preparation method, preferably, in step 4, the inert gas is selected from argon, nitrogen or helium.
[0024] In the above preparation method, preferably, in step 4, the cooling time is 8 to 12 hours.
[0025] On the other hand, the present invention also provides a lithium metal surface protection material, which is prepared by the above method.
[0026] On the other hand, the present invention also provides a lithium metal negative electrode material, which is a lithium metal surface protection material (Cu 3 P@Cu) was prepared by mechanical rolling on a lithium sheet and is denoted as Li 3 P@Cu material.
[0027] In the above-mentioned lithium metal negative electrode material, preferably, the thickness of the lithium sheet is 200-400 μm.
[0028] In the above-mentioned lithium metal negative electrode material, preferably, the speed of mechanical rolling is 1 to 5 rpm / min.
[0029] In the above-mentioned lithium metal negative electrode material, preferably, the Li 3 The P@Cu material further undergoes an interfacial reaction in the electrolyte to construct a mixed conductive intermediate layer, denoted as Li 3 P@CuMCI material.
[0030] The present invention adopts room temperature method to transfer copper phosphide (Cu) on Li metal foil through mechanical rolling process. 3 P) array, in this process, through the metal Li and Cu 3 The interface reaction between P and lithium phosphide (Li 3 The Cu particles are surrounded by a P) network to form a 3D mixed ionic / electronic conductive interlayer (MCI) for interfacial charge redistribution. This method is simple to operate and the stability time of the lithium metal anode is also long.
[0031] On the other hand, the present invention also provides a lithium-ion battery, which includes a lithium metal negative electrode material further prepared from the lithium metal surface protection material prepared by the above method, or a lithium metal negative electrode material prepared from the above lithium metal surface protection material, or the above lithium metal negative electrode material.
[0032] Beneficial effects of the present invention:
[0033] (1) During the preparation of the lithium metal surface protection material of the present invention, the interface of the copper foil synthesized by vapor phase phosphating is uniform, and the Cu 3 P is attached to the surface of copper foil. During the later rolling process and the synthesis process, Cu 3 The P array can be spontaneously transformed into Li 3 Nanoscale materials surrounded by P network;
[0034] (2) The copper phosphide (Cu phosphide) was transferred onto the Li metal foil by mechanical rolling process at room temperature. 3 P) array, in this process, through the metal Li and Cu 3 The interface reaction between P and lithium phosphide (Li 3 P) network surrounded by Cu particles, forming a 3D mixed ion / electronic conductive intermediate layer (MCI) for interfacial charge redistribution, which is used for interfacial charge redistribution and improving the cycle stability of lithium metal anode. This method is simple to operate, greatly shortens the process flow, process time and cost, and the stability time of lithium metal anode is also longer.
[0035] (3)Li 3 The P@MCI interface forms a three-dimensional conductive network with higher stability and multiple ion channels, which can accelerate the transmission performance of Li ions.
[0036] (4) Compared with lithium-based batteries, the lithium metal battery prepared by the method of the present invention has a higher conductivity than the symmetrical battery at 1 mA cm -2 An extended life of over 1,500 hours was achieved at a current of 2.5 volts with slight polarization, further improving the battery’s reaction rate performance and stability.
[0037] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the following is a detailed description of the preferred embodiments of the present invention in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0039] Figure 1 This is a schematic diagram of the process flow for preparing the lithium metal surface protection material and the lithium metal negative electrode material in Example 1 of the present invention.
[0040] Figure 2 The present invention Cu(OH) 2 @Cu foil layer (i.e. Cu(OH) in the figure) 2 Nanoparticles), Cu 3 P@Cu and Li 3 SEM comparison of P@Cu MCI layer (i.e., Li@MCI layer in the figure).
[0041] Figure 3 For the present invention 3 SEM comparison of P@Cu MCI layer and pure bare Li wafer.
[0042] Figure 4 The electrochemical performance comparison diagram of the synthetic material of the present invention and the control group material as negative electrodes is as follows:
[0043] (a) Impedance spectrum of LFP||Li; (b) Impedance spectrum of LFP||Li@MCI (c) Comparison of charge transfer impedance of LFP||Li and LFP||Li@MCI.
[0044] Figure 5 This is a comparison chart of the battery cycle performance of the LFP||Li@MCI buckle battery of the present invention and the LFP||Li buckle battery of the control group.
[0045] Figure 6 This is a comparison diagram of the surface state of the lithium sheet after the battery reaction between the LFP||Li@MCI buckle battery of the present invention and the LFP||Li buckle battery of the control group. DETAILED DESCRIPTION
[0046] The technical solutions in the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. The process, conditions, reagents, experimental methods, etc. for implementing the present invention, except for the contents specifically mentioned below, are all common knowledge and common common sense in the art, and the present invention does not particularly limit the contents.
[0047] Embodiment 1:
[0048] This embodiment provides a method for preparing a lithium metal surface protection material, comprising the following steps:
[0049] (1) Weigh 41.7 mL of concentrated hydrochloric acid and add it to deionized water. Mix and dilute to 500 mL to prepare 500 mL of 1 M hydrogen chloride solution.
[0050] (2) Weigh 1 g of copper foil and add it to the hydrogen chloride solution in step (1) to soak for 10 minutes. Then take out the copper foil and rinse it with deionized water and anhydrous ethanol respectively to remove impurities.
[0051] (3) Prepare 500 mL of a mixed solution of 0.1 M ammonium persulfate and 2 M NaOH, then place the cleaned copper foil in the mixed solution for reaction for 10 min, then take out the copper foil and rinse it with deionized water and anhydrous ethanol respectively, at this time, a copper hydroxide nanosheet layer is formed on the surface of the copper foil, and after washing, air-dry it in air for 4 h to obtain a product, which is named Cu(OH) 2 @Cu foil layer; its SEM image is shown in Figure 2 (a) in .
[0052] (4) Cu(OH) 2 @Cu foil layer and excess sodium hypophosphite are placed in a high temperature resistant porcelain boat; then the Cu(OH) 2 The porcelain boat with @Cu foil layer was placed at the end of the tube furnace, and the porcelain boat loaded with excess sodium hypophosphite was placed at the center of the tube furnace, with a distance of 2 to 4 cm between the two porcelain boats; the temperature of the tube furnace was set to 300 °C, the heating rate was set to 5 °C / min, the gas atmosphere in the tube furnace was argon, the calcination time was 30 min, and the product was taken out after cooling to room temperature after the reaction was completed, recorded as Cu 3 P@Cu, a lithium metal surface protection material; its SEM image is shown in Figure 2 (b) in .
[0053] This embodiment also provides a lithium metal negative electrode material, such as Figure 1As shown, the preparation method is as follows:
[0054] Prepare a lithium sheet with a thickness of 300 μm and place the Cu prepared in the above embodiment on 3 P@Cu is rolled onto the surface of the lithium sheet by mechanical rolling method at a rolling speed of 2rpm / min. After the rolling is completed, the lithium sheet is taken out to obtain Li 3 P@Cu material.
[0055] from Figure 2 As can be seen in (a), the Cu(OH) 2 Nanoparticles are elongated and Figure 2 (b) Cu 3 P@Cu nanoparticles are completely different. The Cu with a diameter of 100nm 3 P nanorods are arranged into a favorable array structure, compared with Cu(OH) 2 Nanoparticles appear as tubular structures at the microscopic level, and the overall structure is an array with a relatively orderly arrangement.
[0056] This embodiment also provides a lithium ion battery, and the assembly method thereof is as follows:
[0057] (1) 10 g of lithium iron phosphate (LFP), conductive carbon black (SP) and polyvinylidene fluoride (PVDF) were weighed in a mass ratio of 8:1:1, NMP was added for dispersion and the solid content was adjusted to 60%, and then the dispersion was carried out at 600 rpm for 5 min and then the speed was adjusted to 2000 rpm for high-speed dispersion for 30 min to obtain a mixed slurry;
[0058] (2) coating the mixed slurry on aluminum foil with a 200 μm scraper, and then drying it in a forced air drying oven at 110° C. for 1 h to obtain a positive electrode sheet;
[0059] (3) Li prepared in the above embodiment 3 The P@Cu material was sliced and vacuum dried according to the procedure of button assembly, and then put into an argon glove box (with water content <1ppm and oxygen content <1ppm) for assembly. During the assembly process, electrolyte was added (Li 3 P@Cu material will form Li 3 P@CuMCI material), the injection liquid is carbonate: diethyl carbonate: dimethyl carbonate (EC:DEC:DMC) with a volume ratio of 1:1:1 1M LiPF 6 solution and 5.0% FEC. During the assembly process, LFP material was used as the positive electrode, Li 3 The P@Cu material was used as the negative electrode and cut into small discs of 12 mm, which were then assembled into a CR2032 half-cell in a glove box, in which a ceramic diaphragm was used as the diaphragm.
[0060] (4) The assembled buckle battery is sealed and activated at 35°C for 12 hours to prepare a lithium-ion buckle battery, namely: LFP||Li@MCI.
[0061] The control group used pure bare lithium sheet materials, which were sliced and vacuum dried according to the procedure of buckle assembly, and then assembled in a glove box. During the assembly process, electrolyte was added, and the injection was 1M LiPF with a volume ratio of carbonate: diethyl carbonate: dimethyl carbonate (EC: DEC: DMC) of 1:1:1. 6 solution and 5.0% FEC. During the assembly process, LFP material is used as the positive electrode and pure bare lithium sheet is used as the negative electrode. It is assembled into a CR2032 half-cell in a glove box, in which a ceramic diaphragm is used as the diaphragm.
[0062] The assembled buckle battery was sealed and activated at 35°C for 12 hours to prepare a lithium-ion buckle battery, namely: LFP||Li.
[0063] from Figure 2 In (c), it can be seen that the uniform portion of the Li@MCI sheet is in the middle layer, with a thickness of about 7.9 μm. 3 The SEM images of the P@Cu MCI layer and the pure bare lithium sheet of the control group are shown in Figure 3 As shown. Figure 3 By comparison, we can see that: Figure 3 In (b), Li@MCI is a dense network layer structure with uniform distribution of Li. Figure 3 The uneven distribution of the layers on the surface of the bare Li wafer in (a) indicates the difference in current density, which means that the formed Li@MCI has more advantages in structure.
[0064] The performance test of the buckle of the above embodiment and the control group is carried out, and the specific test process is as follows:
[0065] Let stand for 2h→rate charge 0.1C, voltage cut off at 3.75V→let stand for 10min→constant voltage charge, current cut off at 0.005A→constant current discharge 0.1C, voltage cut off at 2V→let stand for 10min→rate charge 0.1C, voltage cut off at 3.75V→let stand for 10min→constant voltage charge, current cut off at 0.005A→constant current discharge 0.1C, voltage cut off at 2V→let stand for 10min→rate charge 0.1C, voltage cut off at 3.75V→let stand for 10min→
[0066] Figure 4 This is an analysis and comparison of the impedance spectra of LFP||Li and LFP||Li@MCI. Figure 4(a) is the impedance spectrum of LFP||Li after different cycles. It can be seen from the figure that with the increase of the cycle period, the overall impedance first decreases and then increases. In the first cycle, the overall impedance of LFP||Li is 200Ω. Figure 4 (b) is the impedance spectrum of LFP||Li@MCI after different cycles. It can be seen from the figure that with the increase of the cycle period, the overall trend is consistent with LFP||Li. In the first cycle, the overall impedance of LFP||Li is 16Ω, which is nearly 1 / 12 of the overall impedance of LFP||Li. Figure 4 (c) Analysis of the charge transfer impedance in the impedance spectrum. From the analysis results, it can be seen that the charge transfer impedance of LFP||Li@MCI is much smaller than that of LFP||Li, further indicating that the newly synthesized interface has strong conductivity and stability.
[0067] Depend on Figure 5 It can be seen that the discharge capacity of LFP||Li@MCI can be restored to 130.0mAh / g when the rate changes from 5C to 1C. More importantly, at a rate of 1C, after 300 cycles, the capacity is 119.2mAh / g, and the capacity retention rate is 91.7%. On the contrary, due to the depletion of electrolyte caused by dendrite formation, the discharge capacity of LFP||Li full battery drops sharply after 120 cycles, and only has a capacity of 25mAh / g after 300 cycles, with serious capacity decay.
[0068] Depend on Figure 6 It can be seen that: Figure 6 In (a), the lithium sheet after the LFP||Li full battery reaction is covered with a thick layer of black substrate, and the original bright and shiny lithium foil turns black. Figure 6 In (b), the surface of the LFP||Li@MCI full battery is clean. After cycling in the charging state, the battery is fully charged and the surface of the material synthesized in this implementation case is still bright.
[0069] The present invention uses specific embodiments to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. At the same time, for those skilled in the art, according to the idea of the present invention, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as a limitation on the present invention.
Claims
1. A method for preparing a lithium metal surface protection material, characterized in that: The steps include: Step 1, soaking the copper foil in a hydrogen chloride solution, and then washing to remove impurities; Step 2, mixing the ammonium persulfate solution and the sodium hydroxide solution to obtain a mixed solution; Step 3, placing the impurity-removed copper foil into the mixed solution for reaction, forming a copper hydroxide layer on the surface of the copper foil, washing and drying to obtain a product, which is recorded as Cu(OH)2@Cu foil layer; Step 4: Place the Cu(OH)2@Cu foil layer at the end of the tube furnace, place an excess of sodium hypophosphite at the center of the tube furnace, heat at high temperature in an inert gas atmosphere for reaction, and obtain the product after cooling, which is recorded as Cu3P@Cu, i.e., lithium metal surface protection material.
2. The method according to claim 1, characterized in that: In step 1, the concentration of the hydrogen chloride solution is 1 to 5 M; Preferably, deionized water and ethanol are used for washing respectively.
3. The method according to claim 1, characterized in that: In step 2, the concentration of the ammonium persulfate solution is 0.1 to 1 M; Preferably, the concentration of the sodium hydroxide solution is 2-10M.
4. The method according to claim 1, characterized in that: In step 3, the copper foil after impurity removal is placed in the mixed solution for a reaction time of 5 to 30 minutes; Preferably, deionized water and ethanol are used for cleaning respectively; Preferably, the drying is carried out in air for 4 to 24 hours.
5. The method according to claim 1, characterized in that: In step 4, the distance between the Cu(OH)2@Cu foil layer and the sodium hypophosphite is 2 to 10 cm; Preferably, the temperature of the tube furnace is set to 300-500°C; the heating rate is 2-10°C / min; Preferably, the inert gas is selected from argon, nitrogen or helium; Preferably, the cooling time is 8 to 12 hours.
6. A lithium metal surface protection material prepared by the method according to any one of claims 1 to 5.
7. A lithium metal negative electrode material, characterized in that: The lithium metal negative electrode material is prepared by rolling the lithium metal surface protection material (Cu3P@Cu) described in claim 6 onto a lithium sheet by a mechanical rolling method, and is recorded as Li3P@Cu material.
8. The lithium metal negative electrode material according to claim 7, characterized in that: The thickness of the lithium sheet is 200 to 400 μm; Preferably, the speed of the mechanical rolling is 1-5 rpm / min.
9. The lithium metal negative electrode material according to claim 7, characterized in that: The Li3P@Cu material further undergoes an interfacial reaction in the electrolyte to construct a mixed conductive intermediate layer, which is recorded as Li3P@CuMCI material.
10. A lithium-ion battery, comprising a lithium metal negative electrode material further prepared from the lithium metal surface protection material prepared by the method of any one of claims 1 to 5, or a lithium metal negative electrode material prepared from the lithium metal surface protection material of claim 6, or a lithium metal negative electrode material of any one of claims 7 to 9.